Kajian Literatur Penerapan Strategi Citra Merek dan Islamic Branding dalam Meningkatkan Keputusan Pembelian Produk Kecantikan : (Studi Kasus Penerapan Citra Merek pada Benak Konsumen dan Label Halal pada Produk Kecantikan Wardah Exclusive Matte Lipcream) - Firliana, Ika Ananda (Jurnal Manajemen dan Inovasi (MANOVA), 2018)
In the modern era, of course, the Millennial Generation also does not want to be left behind with updates on the beauty products they use. So companies that produce beauty products are also sued for creating product updates. The goal is to make their products run on the market and make a favorite product among teenagers an additional point of its own if the product is in demand by all walks of life. Coupled with evenly embraced Islam in this country, it has made it imperative that a Muslim woman emphasizes criteria in the selection of beauty products labeled as halal. Because this will suit the needs of a Muslim woman. Then on the other hand the manufacturers of beauty products in the creation of products that are in accordance with the development of science and technology, the producers must also balance with the Islamic Branding label on their products. So that its products run in the market, especially Muslim women. The purpose of this researcher is to find out the application of Brand Image Strategy and Islamic Branding in Improving Purchasing Decisions of Beauty Products with Case Study of Brand Image Implementation on Consumer Minds and Halal Labels on Wardah Exclusive Lipcream Beauty Products. In this study using a qualitative descriptive method with reference to the use of literature studies both from journal guides, books, magazines, and the web that has been selected and considered relevant by researchers with the aim as a supporter of the current research. The conclusion in this study is the importance of applying the Brand Image strategy which aims to attach the brand image to the minds of consumers and Islamic Branding which is a halal label in improving the purchasing decision of Wardah Exclusive Lipcream beauty products, especially in Muslim women.